Does shareholder activism help or hinder shareholder value enhancement? : empirical evidence from the UK - Broadhurst, Timothy (Cranfield University, 2009)
Shareholder activism has increasingly become a widespread value enhancement strategy for institutional investors in the UK. However, thus far only one paper has reported a clinical study to analyse its impact on target firms (Becht et al, 2008) in contrast to numerous papers based on US data. The UK differs from the US in a number of institutional arrangements and legal framework. Hence analysis of the UK context may shed further insights into the motivation and impact of shareholder activism. Firstly, I conduct a survey of UK institutional shareholders to understand the scope and magnitude of shareholder engagement in the UK. I find evidence that UK institutional investors are increasing the level of engagement that they conduct with investee companies. Furthermore, my results suggest that investors prefer to engage with companies in private and fear this could be made more difficult if legally mandated engagement or voting disclosure is introduced. Additionally, I find evidence that UK institutional investors are wary of hedge funds as activists and do not feel that their aggressive activism is necessarily in the interests of the institutional investor‟s client‟s interests. Secondly, using a sample of 595 companies targeted by voting by institutional investors abstaining or voting against resolutions at AGM or EGMs, 172 companies targeted through private negotiation, and 29 companies targeted by shareholder resolutions over the period 2002 to June 2007, I attempt to analyse the impact of activist pressure on a large sample of targeted firms in the UK. I find evidence that targeted firms out-perform control firms over a three day window surrounding the targeting indicating a positive stock market reaction, but under-perform over the two and three year periods following the activist‟s intervention when assessed using multi factor benchmarks. This is consistent with existing US literature. I also find limited or no change in operating performance, firm strategy, corporate governance or executive compensation at targeted firms after becoming targets of activism when compared to the matched control firms. Again, this is consistent with US research, although it contradicts findings from the UK study by Becht et al (2008). Overall we find short term enhancement from being targeted by a shareholder activist in the UK, but this value gain is not sustained over the longer term. Thus benefits of activism seem transitory. Finally, using a sample of 370 UK companies in which 39 activist hedge funds disclose substantial shareholdings; and 101 companies UK and EU that were targeted by activist hedge funds through the press over the sample period 2000 to 2007, I conduct an empirical analysis of activism by hedge funds against targeted firms. In contrast to activism by traditional institutional investors I find evidence that hedge fund activism generates significant positive abnormal returns over both the short and long term. Thus it would appear that the more aggressive tactics used by the activist hedge funds is necessary to generate significant shareholder value increases.